Evaluation of the Implementation of Policies on Organizational Structure and Work Procedures in the Technical Implementation Unit for Population Control, Women's Empowerment and Child Protection, Kapetakan District, Cirebon Regency - Usmin Usmin; Suhendra Suhendra; Nurudin Siradj (ijd-demos, 2022)
AbstractOrganization is a receptacle for a collection of people who work together rationally as well as systematically led or controlled to achieve certain goals utilizing the resources contained in it. In this study researchers using the Qualitative typing type with the type of research method are descriptive methods. The locus was conducted in UPT P5A of Kapetakan District, Cirebon Regency, Informer (narasumber) of research is someone who, because he has information, the informer's selection is based on consideration that the informer is considered the most knowledgeable about the problems that will be examined at this time. On this study, the technique of determining informants performed by researchers was the purposive sampling technique. Data collection techniques by performing study libraries and field studies. Data immortality testing includes: improved persistence, triangulation, discussion with with peers, and membercheck. Data analysis techniques used: data collection, data reduction, data presentation, and conclusion withdrawal. Evaluation of Implementation of SOTK Policy in UPT P5A, Kapetakan District, Cirebon Regency. Institution is a process that does not end. Evaluation Factors for Implementation of SOTK Policy in UPT P5A Cirebon Regency Kapetakan District, External Factor Internal factors. The policy evaluation process was carried out in UPT P5A, Kapetakan District, Cirebon Regency, is not yet Optimal, Efficient, Effective, Adequacy, Alignment, Responsiveness, Accuracy. Efforts have been made to optimize the Evaluation of Implementation of SOTK Policy in UPT P5A Cirebon Regency Kapetakan District: Work / Specialization Division, Command / Command, Control Range.Keywords: SOTK, UPT P5A, Policy Evaluation. AbstrakOrganisasi adalah wadah bagi kumpulan orang yang bekerja sama secara rasional serta sistematis dipimpin atau dikendalikan untuk mencapai tujuan tertentu dengan memanfaatkan sumber daya yang terkandung di dalamnya. Dalam penelitian ini peneliti menggunakan tipe tipe Kualitatif dengan tipe metode penelitian adalah metode deskriptif. Lokus dilakukan di UPT P5A Kecamatan Kapetakan Kabupaten Cirebon Informan (narasumber) penelitian adalah seseorang yang karena memiliki informasi, pemilihan informan didasarkan pada pertimbangan bahwa informan dianggap paling mengetahui masalah yang akan dihadapi. diperiksa saat ini. Pada penelitian ini, teknik penentuan informan yang dilakukan oleh peneliti adalah dengan teknik purposive sampling. Teknik pengumpulan data dengan melakukan studi pustaka dan studi lapangan. Pengujian keabadian data meliputi: peningkatan ketekunan, triangulasi, diskusi dengan teman sebaya, dan membercheck. Teknik analisis data yang digunakan: pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Evaluasi Implementasi Kebijakan SOTK di UPT P5A Kecamatan Kapetakan Kabupaten Cirebon. Kelembagaan adalah proses yang tidak berakhir. Faktor Evaluasi Pelaksanaan Kebijakan SOTK di UPT P5A Kabupaten Kapetakan Kabupaten Cirebon, Faktor Eksternal Faktor Internal. Proses evaluasi kebijakan yang dilakukan di UPT P5A Kecamatan Kapetakan Kabupaten Cirebon belum Optimal, Efisien, Efektif, Kecukupan, Keselarasan, Responsiveness, Ketepatan. Upaya yang telah dilakukan untuk mengoptimalkan Evaluasi Pelaksanaan Kebijakan SOTK di UPT P5A Kabupaten Kapetakan Kabupaten Cirebon : Bagian Kerja/Spesialisasi, Komando/Komando, Rentang Kendali.Kata kunci: SOTK, UPT P5A, Evaluasi Kebijakan.